PENGARUH LINGKUNGAN KERJA FISIK DAN LINGKUNGAN KERJA NON FISIK TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi Pada Karyawan Bagian Weaving PT. Primatexco Indonesia) - Untung, Dasio; Nugraheni, Rini (Diponegoro Journal of Management, 2017)
This research purposes to finding the effect of physical work environment and non-physical work environment to employee performance through job satisfaction as intervening variabel (study on employees of unit weaving PT. Primatexco Indonesia).Data collected through distribution of questionnaires to 70 employees of unit weaving PT. Primatexco Indonesia with non random sampling. The techniques of data testing in this research includes validity test, reliability test, the classical assumption test, multiple linear regression, and the Sobel test to examine the mediation effect with software SPSS version 16 for Windows.The results of this research indicates that physical work environment has positive and significant influence on the job satisfaction, non-physical work environment has positif and significant influence on job satisfaction, physical work environment has positive and significant influence on the employee performance, non-physical work environment has positive influence but not significant on the employee performance, job satisfaction has positif influence but not significant on the employee performance, and job satisfaction hasn’t mediation effect on physic work environment and non-physic work environment to employee performance.